Preferensi Pakan, Tingkah Laku Makan dan Kebutuhan Nutrien Rusa Sambar (Cervus unicolor) dalam Usaha Penangkaran di Provinsi Jambi - . Afzalani; R A Muthalib; E Musnandar (Faculty of Animal Science, Bogor Agricultural University, 2008)
This experiment was conducted to study feed preference, eating behaviour, feed intake, feed digestibility as well as determination of protein and energy requirement for maintenance. This experiment was conducted at Wisata Angsana Garden and Animal Nutrition Laboratory of Animal Husbandry Faculty, Jambi University. One male and two female of Sambar deers with body weight ± 140 kg were used in this experiment. The animals were kept in free stall of 30x15 m. The experiment was divided into three steps: feed preference, eating behaviour and determination of maintenance requirement. The results indicated that Sambar deers preferred Asystasia spp leaf, Hyampeacne amplexicaulis, Axonopus compresus and Cynodon dactylon grasses. Over 12 hours, Sambar deers had eating activity of 319.45±19.35 minutes, rumination activity of 266.85±13.67 minutes, with a total rumination period of 8.16±0.43 and rumination cycles of 30.63±0.79 times per periode. Sambar deers had intake and digestibility of dry matter, crude protein, organic matter, crude fiber, and energy 2.43 kg, 0.66 kg, 2.15 kg, 0.37 kg, 9703.08 kkal GE per day and 74.38±5.22; 77.35±4.61; 87.87±2.47; 51.36±9.91; 67.89±6.54%, respectively. Sambar deers required protein and energy for maintenance as much as 0.44 kg per day or 3.17 g per kg BW and energy 5062.85 kkal DE per day or 36.16 kkal DE per kg BW. Key words: feed preference, eating behaviour, nutrient requirement, Sambar deer